Diseño de un plan de negocio para la producción de bolsas a base de fibra extraída de las hojas de la planta de piña en la ciudad de Bogotá (2021)
He following work presents a business plan for the production and marketing of Fibre-based bags extracted from the leaves of the pineapple plant. First, an analysis of the product to be marketed is presented, presenting characteristics that have an added value, generating a culture that is friendly to the planet. A market analysis is carried out through a survey, where the Percentage of people who would be willing to use the product in order to reduce the consumption of plastic bags that all it does is a bad to our environment, after this an operational analysis was presented where the process of production of these packaging was translated, finally a financial analysis was carried out to measure the viability of the project.